Criteria for feasibility, health and welfare assessment of requirement to use second and subsequent generations of non-human primates or animals from self-sustaining colonies in research - Thierry Decelle; Lars Friis Mikkelsen; David Smith; Magda Chlebus (Revue de Primatologie)
The European Directive 2010/63/EU on the protection of animals used for scientific purposes requires that a feasibility study must be conducted by the European Commission to determine if all sourcing of non-human primates from parents bred in captivity (F2) or from self-sustaining colonies can be achieved. This study should also include an assessment of animal health and welfare. Prior to the initiation of the European Commission’s study, it was considered by EFPIA and FELASA that the criteria to be used in the feasibility, health and welfare assessment should be established by experts to help expedite such a study. This paper identifies those criteria which may be useful in making policy decisions on the confirmation or reconsideration of the timetable for implementation of the F2 requirement. A key requirement before a number of criteria can be assessed is the generation of base-line data relating to the supply and future demand of non-human primates and the health and welfare status of current breeding colonies supplying the European market. Three groups of criteria have been indentified, namely feasibility, science and research and welfare. Within each group, a number of parameters are defined and their rationale for inclusion, together with suggested information points, is discussed.